Vitamin D Deficiency and its Association with Respiratory Tract Infections in Pediatrics: Life Sciences-Pharma - Balaprabha, G.Ramya; Hakeem, Jumana; Sanjana, Kodakandla; Avanish Reddy, Illuri; Alekhyamuliki; Koppula, Pradeep Kumar; Rao, T.Rama (International Journal of Life Science and Pharma Research, 2022)
Respiratory tract infections (RTI) are a major cause of mortality and morbidity in children. Several studies have aim supplementation as a possible preventive measure against respiratory tract infections in children. Vitamin-D (sunshine vitamin) is a type of prohormone with various functions like extracellular calcium ion maintenance, immunomodulation in the body. The three major sources of Vitamin-D are Sun exposure, Diet and Supplements. The main objective of our study was to correlate the vitamin D deficiency in children with RTI’s. A prospective observational study was conducted for 6 months inpatient of the Pediatric department in tertiary care hospital. Demographic details, cause of admission, past medical and medication history, feeding history, sun exposure was taken by interviewing the guardian. Data of a total of 25 pediatric patients with various respiratory tract infection cases were collected, documented and their vitamin D levels were analyzed in our study. The vitamin D level of samples was analyzed by Electro chemiluminescence immunoassay. Statistical methods were applied and significant differences were observed among the vitamin D sufficient and deficient patients with RTI’s. It was observed that out of 25 cases, 16 cases had recurrent respiratory tract infections and 9 had non-recurrent respiratory tract infections which statistically shows P value < 0.05. This study significantly correlates vitamin D deficiency with respiratory tract infections in children. This study also suggests vitamin D as a supplement therapy as it plays an important role in the innate and the adaptive immunity.